Impact of Agricultural activities on water quality in the Dufuya Dambos, Lower Gweru, Zimbabwe - Muzvondiwa, John Vengai; Gono, Robert Kudzanayi; Sichewo, Petronillah Rudo (IJSR, 2022)
Recently, concern over agricultural diffuse pollution sources in integrated water quality management has been growing. High inorganic and organic fertilisers application rates may increase groundwater pollution and these effects were investigated in the Dufuya Wetland (19 o 17’S; 29o 21’E) in Chief Sogwala area of Lower Gweru Communal Lands, approximately 42km west of the City of Gweru, Zimbabwe. Forty-two (42) water samples were collected for analysis of pH, conductivity, calcium, nitrates, and phosphates during the months of September, October, and November 2008. A questionnaire procedure was used for collection of manure application rate, wetland and crop management data in the studied area. The results demonstrated that cattle manure in the Dufuya wetland is applied at the rate of 30t/ha- 60t/ha per year. Groundwater and surface runoff water samples have pH, conductivity, calcium, phosphates and nitrates levels within the WHO permissible guideline of 6.5-8.5, 1500μScm-1 , 200mg/l, 0.09mg/l and 10mg/l respectively. The mean nitrate and phosphate concentrations in surface run-off water in the garden and the sponge are 0.00275mg/l, 0.0117mg/l and 0.00377mg/l, 0.00077mg/l respectively. Groundwater concentrations are 0.026mg/l, 0.0167mg/l and 0.0021mg/l, 0.00228mg/l for nitrates and phosphates respectively. There was no significant difference in the mean concentrations of nitrates and phosphates in water (ground/surface) in the sponge and the garden (P < 0.005). Fertiliser applications have no negative effects on dambo water quality.